Karaim language studies – a historical overview - Jankowski, Henryk (Vilnius University Proceedings, 2024)
The aim of this paper is to put forth a short overview of the study in the Karaim language. Firstly, the position and importance of Karaim is stressed. Secondly, trends in research are demonstrated. Thirdly, general descriptions, grammars, and dictionaries are presented. The article highlights the most significant studies in the basic domains of Karaim linguistics such as phonetics and phonology, morphology, syntax, lexicology, and semantics. At the same time, the article formulates several postulates for tasks to be done. A selected bibliography of most relevant studies has also been included.